When are similar regimes more likely to form alliances? Institutions and ideologies in the post-communist world. Issue 2 (3rd March 2016) - Horowitz, Shale; Tyburski, Michael
Abstract : Following the collapse of the old communist regimes, 28 post-communist countries chose from among three main foreign security arrangements: commonwealth of independent states (CIS)/collective security treaty organization (CSTO) membership, north atlantic treaty organization (NATO) membership, or neutrality. What explains these choices? We are most interested theoretically in the role played by regime type. The alliances literature typically uses a narrow institutional theory of the effects of regime type, which implies that more democratic regimes are more attractive alliance partners than more authoritarian regimes. Post-communist area specialists will be aware that this institutional theory fails to explain the apparent tendency of more authoritarian post-communist regimes to join the CIS/CSTO. We develop a broader ideological theory of how regime type affects alliances, in which political institutions are complemented by substantive ideological and policy goals. Applying the ideological approach to the post-communist world, we define and measure two main ideological regime types – liberal nationalist regimes and neo-communist authoritarian regimes. Multinomial logit regressions indicate that more democratic, liberal nationalist regimes are more likely to affiliate with NATO, whereas more authoritarian, neo-communist regimes are more likely to join the CIS/CSTO. Moreover, the desire of neo-communist authoritarianism regimes to affiliate with the CIS/CSTO is as strong or stronger than that of neo-liberal democracies to affiliate with NATO – largely because NATO is more reluctant than Russia to accept aspirants. We conclude that the ideological approach to regime type may offer significant explanatory value as a refinement of the institutional approach.